Analysis of interpretive structural model of Indian railway security system by analytic hierarchy process (AHP). Issue 3 (15th July 2019) - Srivastava, Anoop; Gaur, Sant Kumar; Swami, Sanjeev; Banwet, D.K.
Abstract : Purpose: Security and safety have remained important concerns for mankind since ancient times. In the context of railways, however, the threat perceptions to safety and security have increased significantly lately. In view of this, the Indian Railways requires an effective and efficient security management system. The purpose of this paper is to propose an integrated approach to help develop the Indian railway security system (IRSS) by successively reducing the complexity of the system through a series of studies. Design/methodology/approach: The relevant elements of the complex system of Indian Railways have been identified. The framework in which the elements exist and interact with each other has been clearly established using the interpretive structural modelling (ISM) technique. The output of ISM is further reduced in complexity by having different policy option profiles. A comparison of different option profiles has been done by a multi-criteria decision-making technique, the analytic hierarchy process (AHP), by choosing suitable criteria for comparison. Findings: The following elements need to be pursued as the key objectives for making IRSS: protection of passengers, protection of property, modernisation, manpower enhancement, multi-skilling of staff, latest technology and enhanced legal powers. Research limitations/implications: The present research can be extended in many important ways. Interpretive structural models for different contextual relationships can be developed and used for formulating and implementing customised security policy. Policy elements and the ISM structure obtained in this research can be utilised for the system dynamic modelling of IRSS. A pilot study can be done to implement the recommendations made in this study. Practical implications: The ISM model developed can be implemented as a policy tool in enhancing the railway's security. Some of the policy elements proposed appear to be consistent with the strategic direction being undertaken in the railway security in the country. Social implications: Security is an important concern for mankind and social civilisations. The results have significant welfare implications in India and the rest of the world. Originality/value: The present study is one of the first approaches in a series of studies in railway security in India. The results of this study can be extended to other security scenarios with similar needs.